Comparison of laparoscopic hepaticojejunostomy and open hepaticojejunostomy. Can stenosis of the hilar hepatic duct affect postoperative outcome?. Issue 3 (30th January 2017) - Miyano, Go; Koyama, Mariko; Miyake, Hiromu; Kaneshiro, Masakatsu; Morita, Keiichi; Nakajima, Hideaki; Yamoto, Masaya; Nouso, Hiroshi; Fukumoto, Koji; Urushihara, Naoto
Abstract: Introduction: The aim of this study was to compare laparoscopic hepaticojejunostomy (LHJ) and open hepaticojejunostomy (OHJ) for choledochal cyst associated with hilar hepatic duct stenosis (HHDS). Methods: Data collection was prospective for LHJ cases from 2009 and retrospective for OHJ cases from 2003 to 2008. Data were compared with respect to HHDS. HHDS was incised longitudinally as required during hilar hepatic ductoplasty. Results: Fifty‐eight subjects were studied (LHJ: n  = 27, 4 boys, 23 girls; OHJ: n  = 31; 6 boys, 25 girls). HHDS was present in 10 LHJ cases and 10 OHJ cases. Todani classification of choledochal cyst in LHJ patients was type 1A ( n  = 16) and type 4A ( n  = 11), and in OHJ patients, it was type 1A ( n  = 19) and type 4A ( n  = 12). There were significant differences between LHJ and OHJ with regard to mean operative time (386 vs 341 min), mean blood loss (5.9 vs 18.4 mL), recommencement of enteral feeding (3.9 vs 6.4 days), and hospital stay (11.7 vs 15.5 days) (all P  < 0.05). Hepatic ductoplasty was performed in 23 LHJ patients and in 21 OHJ patients. There were no intraoperative complications and no conversions to OHJ. There were no significant differences between LHJ and OHJ, regardless of the presence of HHDS, for postoperative complications, which included minor bile leakage, anastomotic stricture, and intestinal obstruction. Conclusion: LHJ is as effective as OHJ for the treatment of choledochal cysts irrespective of the presence of HHDS and the need for hepatic ductoplasty.